Effect of Low Nutrient Density Diets on Performance of Vanaraja Laying Hens in Intensive System of Production - Panda, Arun Kumar (Indian Journal of Animal Nutrition, 2021)
An experiment was conducted to evaluate the effect of low nutrient density diets on production performance, egg quality and serum biochemical parameters of Vanaraja laying hens in the intensive system. A total of 72 Vanaraja laying hens were randomly distributed into three dietary treatment groups with fourreplicates in each group with 6 birds in each pen. These birds were reared in dip litter system under uniform management conditions throughout the experimental period (28-44 wk). A standard diet (control diet) containing 2600 kcal/kg ME, 16% CP, 0.7% lysine and 0.35% methionine was formulated. Subsequently, two low nutrient density diets were formulated by reducing the above nutrients by 3 and 6%. The levels of calcium and non-phytate phosphorus were constant in all the three diets. A measured quantity of each diet was fed toone of the treatment groups for a period of 12 weeks to study their performance. The birds fed control diet gained significantly higher weight of 45.36 g during the experimental period. Reducing the nutrient density byeither 3 or 6% resulted in negative growth and birds lost body weight by 24.10 and 48.21g, respectively. The hen housed egg production, egg weight, egg mass per day and feed efficiency did not differ among the dietary group due to reduction in nutrient density of the diet. None of the egg quality parameters (% albumen, % yolk, % eggshell, shell thickness and Haugh unit) differed significantly due to reduction in the density of diets in Vanaraja laying hens. The concentrations of serum protein, albumin, globulin, triglycerides and totalcholesterol, were not influenced due to reduction in the nutrient density by upto 6% in the diets. However, the serum concentrations of uric acid and creatinine was significantly decreased in the diet with 6% reduction in nutrient density compared to either control or 3% reduced nutrient density diet. It is concluded that the nutrient density can be reduced to 6% of the control diet and diet containing 2440 kcal/ME per kg diet, 15.0% CP, 0.66 % lysine and 0.33% methionine could be adequate in maintaining optimum performance of Vanarajalaying hens.